Moving fluoroscopy-based analysis of THA kinematics during unrestricted activities of daily living - D’Isidoro, Fabio; Brockmann, Clara; Friesenbichler, Bernd; Zumbrunn, Thomas; Leunig, Michael; Ferguson, Stephen J. (Frontiers in Bioengineering and Biotechnology, 2023)
Knowledge of the accurate in-vivo kinematics of total hip arthroplasty (THA) during activities of daily living can potentially improve the in-vitro or computational wear and impingement prediction of hip implants. Fluoroscopy-based techniques provide more accurate kinematics compared to skin marker-based motion capture, which is affected by the soft tissue artefact. To date, stationary fluoroscopic machines allowed the measurement of only restricted movements, or only a portion of the whole motion cycle. In this study, a moving fluoroscopic robot was used to measure the hip joint motion of 15 THA subjects during whole cycles of unrestricted activities of daily living, i.e. overground gait, stair descent, chair rise and putting on socks. The retrieved hip joint motions differed from the standard patterns applied for wear testing, demonstrating that current pre-clinical wear testing procedures do not reflect the experienced in-vivo daily motions of THA. The measured patient-specific kinematics may be used as input to in vitro and computational simulations, in order to investigate how individual motion patterns affect the predicted wear or impingement.